KETANGGUHAN MASYARAKAT PESISIR DI KECAMATAN PEKALONGAN UTARA TERHADAP BANJIR ROB - AKHMAD, GILANG RUSADI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The coastal areas are often subjected to flood which also happened at North Pekalongan Sub District. The vulnerability of coastal community to coastal flooding was being worsened by the intensity of the flood itself and the economic condition of the citizen that is mostly daily workers. Therefore to reduce vulnerability can be achieved by increasing the resilience. Resilience is built on five basic assets i.e. natural, physical, economic, human, and social asset. Evaluation of coastal community resilience against tidal flood was conducted at Bandengan, Kandang Panjang, and Panjang Baru Village, on 40 respondents for each village. Result of interview, field observation, and set of secondary data were analyzed descriptively. The results showed that Kandang Panjang had the highest score on economic, human, and social asset. This resilience analysis also showed that human asset, i.e. level of education achievement and job skill is the most essential and fundamental asset of all to build a resilient community. Community that have a good level of education achievement and job skills have a great opportunity to work in the formal sector. Residents as retirees, factory workers, and civil servants were not experiencing reduced income. Human assets such as level of education echievement and job skills also incluence to natural, physical, and social asset. Keywords: resilience, coastal community, North Pekalongan Sub District